2023
DOI: 10.1093/jas/skad134
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of a bacterial 6-phytase supplemented beyond traditional dose levels on jejunal mucosa-associated microbiota, ileal nutrient digestibility, bone parameters, and intestinal health, and growth performance of nursery pigs

Abstract: This study aimed to determine the efficacy of a bacterial 6-phytase (Buttiauxella spp.) supplemented beyond traditional dose levels based on jejunal mucosa-associated microbiota, apparent ileal digestibility (AID), intestinal health and bone parameters, and growth performance of nursery pigs. Seventy-two weaned pigs (36 barrows and 36 gilts at 21 d of age with 5.8 ± 0.5 kg BW) were allotted to six treatments based on randomized complete block design with sex and initial BW as blocks and fed in three dietary ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 78 publications
2
6
0
Order By: Relevance
“…The deviation between the previous studies [ 3 , 13 ] and this study may be due to the low MDA in the jejunal mucosa of pigs fed control diets without XG, leaving little room for the reduction of MDA content in the jejunum with XG supplementation. However, the MDA content obtained in this study was within a typical value compared to other recent measurements from pigs with similar genetic background and feeding environment [ 29 , 78 – 80 ].…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The deviation between the previous studies [ 3 , 13 ] and this study may be due to the low MDA in the jejunal mucosa of pigs fed control diets without XG, leaving little room for the reduction of MDA content in the jejunum with XG supplementation. However, the MDA content obtained in this study was within a typical value compared to other recent measurements from pigs with similar genetic background and feeding environment [ 29 , 78 – 80 ].…”
Section: Discussionsupporting
confidence: 81%
“…Phytase has been extensively used in pig feeds to release entrapped nutrients, including minerals and energy bound in the form of phytate [ 25 , 26 ]. Phytase also releases proteins, non-selectively bound with phytate, improving enzyme activity, such as trypsin in the small intestine in animals [ 27 , 28 ], potentially altering the nutrient utilization and intestinal microbiota of pigs [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…(2022) . Villus height and crypt depth (VH:CD) were measured using a camera (Infinity 2-2 digital CCD) attached to a microscope (Olympus CX31, Lumenera Corporation, Ottawa, Canada) as described in previous studies ( Deng et al., 2022 ; Moita and Kim, 2023 ). Lengths of 15 well-oriented intact villi and their associated crypts were measured in each slide.…”
Section: Methodsmentioning
confidence: 99%
“…The results of the present study showed that phytase supplemented individually or combined with xylanase and protease increased the ATTD of Ca, P, and ash, whereas xylanase and protease showed most of the benefits to nutrient digestibility when supplemented together and/or in combination with phytase. The positive effects of phytase supplementation for pigs, especially in Ca and P digestibility, has been showing consistency over the last decades [ 19 , 41 , 42 ]. On the other hand, the supplementation of xylanase and protease showed more variable results when compared to phytase, even when combined with other enzymes [ 21 , 27 , 29 ].…”
Section: Methodsmentioning
confidence: 99%
“…The digestibility of P, Ca, and ash can be influenced by various factors, including diet composition, feed processing methods, and the presence of antinutritional factors or feed enzymes in the feed [ 1 , 25 , 38 ]. While there is a relationship between the digestibility of P and Ca due to their interplay in bone formation and mineralization [ 17 , 41 ], the relationship between their digestibility and the digestibility of ash is not always correlated. Studies regarding the effect of dietary supplementation of phytase on P digestibility in DDGS are variable.…”
Section: Methodsmentioning
confidence: 99%